2015
DOI: 10.1016/j.jhep.2015.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Treating liver fat and serum triglyceride levels in NAFLD, effects of PNPLA3 and TM6SF2 genotypes: Results from the WELCOME trial

Abstract: *WELCOME, Wessex Evaluation of fatty Liver and Cardiovascular markers in NAFLD with OMacor thErapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 42 publications
1
75
0
3
Order By: Relevance
“…The PNPLA3 rs738409[G] variation displays a strong interaction with the environment. Indeed, as highlighted above, the increased susceptibility to liver damage observed with rs738409[G] occurs predominantly in the presence of a concomitant liver insult (e.g., obesity, alcohol consumption, viral infection) or in association with increased consumption of certain types of fatty acids [21,102,103]. Although rs738409[G] might not be directly associated with all these risk factors, such as every feature of the metabolic syndrome, these phenotypes may, in fact, trigger the impact of PNPLA3 on steatosis and fibrogenesis and the complex relationships among these factors should not be dissociated.…”
Section: The Contribution Of Pnpla3 To Liver Damage Risk and Its Predmentioning
confidence: 99%
“…The PNPLA3 rs738409[G] variation displays a strong interaction with the environment. Indeed, as highlighted above, the increased susceptibility to liver damage observed with rs738409[G] occurs predominantly in the presence of a concomitant liver insult (e.g., obesity, alcohol consumption, viral infection) or in association with increased consumption of certain types of fatty acids [21,102,103]. Although rs738409[G] might not be directly associated with all these risk factors, such as every feature of the metabolic syndrome, these phenotypes may, in fact, trigger the impact of PNPLA3 on steatosis and fibrogenesis and the complex relationships among these factors should not be dissociated.…”
Section: The Contribution Of Pnpla3 To Liver Damage Risk and Its Predmentioning
confidence: 99%
“…No improvement in the fibrosis scores occurred. Additionally, in a further analysis of the treatment effects in this cohort, although the numbers of subjects with the PNPLA3 148MM genotype was small, there was a suggestion that there was no effect of DHA enrichment to decrease liver fat in patients with this specific PNPLA3 genotype (110). These data provide intriguing evidence for a DHA treatment-PNPLA3 genotype effect, to modify the impact of the treatment with omega-3 fatty acids to decrease liver fat in NAFLD.…”
Section: Clinical Evidence In the Adult Populationmentioning
confidence: 67%
“…Collectively, nine randomized, controlled trials including 964 patients with biopsy-proven NASH, comparing vitamin E, glitazones, pentoxifylline, or obeticholic acid to one another or placebo, were identified. This metaanalysis revealed only moderate-quality evidence for glitazones, pentoxifylline and obeticholic acid to decrease hepatic necroinflammation and for pentoxifylline and obeticholic acid to improve hepatic fibrosis 141 . Taken together, these data do not allow for straightforward recommendations for drug treatment of this disease.…”
Section: Management and Treatment Options For Nafldmentioning
confidence: 92%
“…In contrast, others have shown a benefit of n-3 PUFA treatment on liver fat assessed by magnetic resonance imaging (and have suggested that a greater benefit in NAFLD was associated with docosahexanoic acid treatment) [138][139][140] . Additionally, it has been suggested that the PNPLA3 148MM may attenuate any beneficial effect conferred by n-3 PUFA treatment in NAFLD 141 , emphasizing that future clinical trials testing new potential treatments for NAFLD should also perhaps consider the influence of different genotypes to modify any treatment effect.…”
Section: Management and Treatment Options For Nafldmentioning
confidence: 99%